Innovative Polymeric Adsorbents Radiation-Induced Graft Polymerization - Saito, Kyoichi (Springer Singapore, 2018)
This book presents the reader with a story-based narrative of discovery and development of radiation-induced graft polymerization. The report presented here accomplishes this by relating the inspiring account of research and development based on long-term collaboration among a professor, an engineer, and an entrepreneur. Their goal, ultimately successful, was to come up with a method for grafting functional polymer chains onto existing trunk polymers. The desired outcome was to produce feasible forms for practical use as adsorbents such as porous hollow-fiber membranes, porous sheets, nonwoven fabrics, and fibers. Adsorbents that specifically and efficiently bind to target ions and molecules are essential for capturing uranium species in seawater and antibody drugs in biological fluids and for removing metal ions from ultrapure water and radioactive cesium ions from contaminated water. This unique volume, with its clearly written text and many illustrative figures and diagrams, demonstrates the advantages of the high-adsorption capacity and rate and the easy handling of new polymeric adsorbents over conventional adsorbents. The dynamic behavior of graft chains as described here is certain to appeal especially to chemists, physicists, and material scientists as well as to other readers with an interest in this valuable subject. .